2019
DOI: 10.17765/2176-9206.2019v12n1p9-18
|View full text |Cite
|
Sign up to set email alerts
|

Efeito Da Kinesio Taping No Desempenho Do Salto Horizontal E Vertical Em Atletas Recreacionais De Voleibol

Abstract: O objetivo deste trabalho concentra-se em avaliar os efeitos da Kinesio Taping na potência dos membros inferiores após 24, 48 e 72 horas de aplicação da bandagem, bem como 24 horas após a sua retirada. Trata-se de estudo experimental, com 40 atletas, divididos em grupo placebo (GP) e grupo Kinesio Taping (GKT). Foram avaliados o Single-Leg Hop Test, salto em distância e o teste de impulsão vertical, durante cinco dias consecutivos. Utilizou-se os testes ANOVA, t Student e Mann-Whitney (p ≤ 0,05). No grupo GKT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…[8,13] Besides the studies that evaluated only horizontal jumping, [28,34] many of the studies examining vertical and horizontal jump performance like ours preferred the single leg hop test because it is a reliable and practical method. [4,16,17,22] Contrary to the reports indicating positive effects of KT on horizontal jumping, [4,16] there are also reports in the literature mentioning no such effects. [8,17,22] Similar to these studies, we observed that KT increased horizontal jumping performance in both athletes and sedentary individuals.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…[8,13] Besides the studies that evaluated only horizontal jumping, [28,34] many of the studies examining vertical and horizontal jump performance like ours preferred the single leg hop test because it is a reliable and practical method. [4,16,17,22] Contrary to the reports indicating positive effects of KT on horizontal jumping, [4,16] there are also reports in the literature mentioning no such effects. [8,17,22] Similar to these studies, we observed that KT increased horizontal jumping performance in both athletes and sedentary individuals.…”
Section: Resultsmentioning
confidence: 92%
“…[13][14][15] The number of studies in which both horizontal and vertical jump are considered together is less. [4,16,17] There are many studies investigating the effects of KT on muscle strength, vertical jump, explosive force, pain, inflammation, blood circulation and tissue healing. [14,[18][19][20][21] In order to measure vertical jump and horizontal jump performances, KT was applied on different muscles, and generally the quadriceps femoris muscle was evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations